Flexural and Torsional Analysis of Five Acrylics for Use in External Skeletal Fixation - Davis, M.; Schulz, K. S.; Fawcett, A.; Slater, Margaret R.; Roths, J. B. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Mechanical testing of five acrylics was performed to evaluate material property differences that might affect their use as support rods in external skeletal fixation (ESF). Flexural and torsional analysis demonstrated that differences existed in the stiffness of the acrylics with polyethyl/polymethylmethacrylate products being the stiffest and a polyethylmethacrylate product being least stiff. Increasing the amount of inert filler also increased the stiffness. The inherent porosity of the individual acrylics did not have an effect on their mechanical properties. These differences in stiffness might affect fracture healing by affecting the amount of primary or secondary osteosynthesis that occurs.Different polymeric forms of acrylic possess mechanical properties that influence their stiffness. Based on flexural and torsional analysis, these properties may differ significantly and affect external skeletal fixator stiffness.Presented at the twenty-fourth annual meeting of the Veterinary Orthopedic Society, Big Sky, MT March 2-8, 1997.
Keywords: Acrylics; external skeletal fixation; mechanical analysis